EKSTRAKSI DAN KARAKTERISASI GLUKOMANAN DARI TEPUNG BIJI SALAK (Salacca edulis Reinw.) - Faradisa Anindita; Syaiful Bahri; Jaya Hardi (KOVALEN: Jurnal Riset Kimia, 2016)
This research aims to determine the shaking time and ratio of salak seed flour : anti-solvent isopropyl alcohol to produce glucomannan extract with high yield and high quality. Glucomannan extraction process from salak seed flour is done by aquadest solvent at temperature of 95 °C with shaking speed of 700 rpm for 30, 60, 90, 120, 150, and 180 minutes. Glucomannan precipitate was gained with anti-solvent isopropyl alcohol 95% with salak seed flour : anti-solvent ratio is 1:9, 1:11, 1:13, 1:15, and 1:17 (w/v). Then research using Completely Randomized Design (CRD) at the level of 95%. The results showed the best extraction time was obtained at shaking time of 120 minutes with yield of  21.47% and the best ratio of salak seed flour : isopropyl alcohol is 1: 17 (w/v) with yield of 40.19%. Characteristics of glucomannan is a water content of 11.18%, ash content of 1.2%, and the molecular weight 2.057 x 104 g/mol.Keywords : salak seed flour, shaking time, glucomannan.